2021
DOI: 10.1056/nejmoa2031631
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin or Doxycycline for Asymptomatic Rectal Chlamydia trachomatis

Abstract: BACKGROUNDRectal chlamydia is a common bacterial sexually transmissible infection among men who have sex with men. Data from randomized, controlled trials are needed to guide treatment. METHODSIn this double-blind trial conducted at five sexual health clinics in Australia, we randomly assigned men who have sex with men and who had asymptomatic rectal chlamydia to receive doxycycline (100 mg twice daily for 7 days) or azithromycin (1-g single dose). Asymptomatic chlamydia was selected as the trial focus because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…75% and 100%). Another randomized, double-blind, double-dummy controlled trial in MSM in Australia showed 76% (227/297; 95% CI 74–79) for azithromycin and 97% (281/290; 95% CI 95–99) for doxycycline [ 127 ]. The results from the first controlled trial in women, the are underway [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…75% and 100%). Another randomized, double-blind, double-dummy controlled trial in MSM in Australia showed 76% (227/297; 95% CI 74–79) for azithromycin and 97% (281/290; 95% CI 95–99) for doxycycline [ 127 ]. The results from the first controlled trial in women, the are underway [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…In assessing factors that could predict azithromycin treatment failure, it was consistently shown that a higher baseline rectal CT load was associated with azithromycin treatment failure in MSM and in women [ 116 , 127 , 131 , 132 ]. In women, it was additionally shown that baseline viable rectal CT was key to later viable CT treatment failure [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both treatments are highly effective in urogenital CT 10. Two randomised controlled trials in Men who have sex with men (MSM) demonstrate substantial lower effectiveness of azithromycin in anorectal CT 11 12. An observational study in women (FemCure spin-off) showed similar findings13 and moreover demonstrated that CT treatment failures frequently (in 75%) represented viable CT 4.…”
Section: Introductionmentioning
confidence: 99%